Flexibility Measurement in Production Systems Handling Uncertainties in Industrial Production - Rogalski, Sven.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
The requirements for production systems are constantly changing as a result of changing competitive conditions. This poses a challenge for manufacturers in the various branches of industry and creates an ever-increasing need for flexibility. With this as a background, this book explores the current developments and trends as well as their impact on today$1 (Bs production systems. It also compares known strategies, concepts and methods used to achieve production flexibility. Similarly, the practical knowledge and current research will be drawn upon and subjected to a sound scientific analysis, through which the technical and organizational flexibility ranges can be measured in their application in a production system. The convenience and usefulness of this concept for manufacturers is substantiated by its implementation in a software tool called ecoFLEX and its practical application, based on extensive examples. This illustrates how flexibility flaws can be quickly identified, classified and properly disposed of using ecoFLEX. This tool helps to close the gap between ERP / PPS systems and digital factory planning tools.s
Introduction -- Analysis of the field of observation -- Introduction of a new Evaluation Methodology -- Practical Experience in the new Methodology -- Summary and Outlook -- References -- Appendix A Basic Knowledge -- Appendix B Additional Methods for Calculating of Flexibility -- Appendix C Demonstration of Further Aspects Regarding the Evaluation Methodology -- Appendix D Example of a Production System (for Illustrating Flexibility Calculations) -- Appendix E Calculation Parameters of the Expansion Activities from the Example Production System.
Keywords: Engineering; Information systems; Industrial engineering; Management information systems; Engineering; Industrial and Production Engineering; Information Systems Applications (incl.Internet).; Business Information Systems